The Modelling of Manpower by Markov Chains - A Case Study of the Slovenian Armed Forces - Škulj, D.; Vehovar, V.; Štamfelj, D. (Informatica)
The Modelling of Manpower by Markov Chains - A Case Study of the Slovenian Armed Forces